1. (x+3y-5)dx-(x-y-1)dy=0
Substitutions X=x-2, Y=y-1 is clear from solving stationary point equations:
"\\begin{aligned}\n x+3y-5=0 \\\\\n x-y-1=0\n\\end{aligned}" => "\\begin{aligned}\n x=2 \\\\\n y=1\n\\end{aligned}"
Equation in terms of the variable z was integrated as follows:
"\\frac{dz}{dX}X=\\frac{(z+1)^2}{1-z}" => "\\frac{(1-z)dz}{(z+1)^2}=\\frac{dX}{X}" => "\\frac{2-(1+z)}{(z+1)^2}dz=\\frac{dX}{X}"
Integrating
"\\int\\frac{2-(1+z)}{(z+1)^2}dz=\\int\\frac{dX}{X}" => "\\int\\frac{2dz}{(z+1)^2}-\\int\\frac{dz}{z+1}=\\int\\frac{dX}{X}" =>"-\\frac{2}{z+1}-ln|z+1|=ln|X|-C" => "C=\\frac{2}{z+1}+ln|z+1|+ln|X|"
Remember z=Y/X. So from here
"C=\\frac{2}{\\frac{Y}{X}+1}+ln|\\frac{Y}{X}+1|+ln|X|" => "C=\\frac{2X}{X+Y}+ln|X+Y|"
Comments
Leave a comment